Aid for trade and the political economy of trade liberalization - Georg Koopmann; Ruth Hoekstra (Hamburgisches WeltWirtschaftsInstitut (HWWI), 2010)
The Aid for Trade (AfT) initiative has gained much popularity since its launch at the World Trade Organization's Ministerial Conference in 2005, and there are ongoing discussions on its effectiveness and potential to improve the integration of developing countries into the world economy. This paper contributes to the debate by analyzing AfT in a political economy context. We find that the delivery of AfT is a precondition for trade reform in developing countries, as well as for trade liberalization and trade-enhancing rule-making in regional and international forums. Accordingly, AfT may be a catalyst of trade reforms domestically and internationally.
Keywords: F13; F35; F50; O19; 330; Aid for Trade; Trade Liberalization; Trade Policy; Trade Reform